Design of PC-based sliding mode controller and normalized sliding surface slope using PSO method for robot manipulator. - Sulaiman, Nasri; Piltan, Farzin; Jalali, Amin (2011)
One of the best nonlinear robust controllers which can be used in uncertainty nonlinear systems (e.g., robot manipulator) is sliding mode controller (SMC). Sliding mode controller has two most important challenges in uncertain systems: chattering phenomenon and nonlinear dynamic equivalent part. This research is focused on the applied normalized particle swarm optimization (PSO) tunable gain method in robust classical method (e.g., Sliding Mode Controller) in the presence of uncertainties and external disturbance to reduce the limitations. Applying the boundary layer is the first goal that causes the elimination of the chattering part. Second target focuses on the elimination of chattering phenomenon with regard to the variety of uncertainty and external disturbance; as a result in sliding mode controller adjusting the sliding surface slope coefficient depends on applying PSO method